1997
DOI: 10.1080/0950069970190502
|View full text |Cite
|
Sign up to set email alerts
|

Students’ conceptual patterns of human nutrition

Abstract: The conceptual patterns concerning human nutrition encountered in a sample of students aged between 11 and 17 are described. These patterns show that the conceptual structures of the students were relatively well organized and, although sometimes incomplete or wrong, seemed perfectly coherent to them, even constituting theories that they used to explain any problem situation connected with these processes. The results obtained demonstrate that these patterns are found in all the educational levels examined and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 15 publications
0
10
0
3
Order By: Relevance
“…Students redesign their school lunch and activity choices to balance the calories consumed in their school lunch choices with the calories used up doing their activities. The literature shows that the seven science concepts addressed in this pPBSc are challenging to teach (Arnaudin & Mintzes, 1985;Barak, Gorodetsky, Chipman, & Gurion, 1997;Dreyfus & Jungwirth, 1989;Driver et al, 1997;Gayford, 1986;Lijnse, 1990;Mintzes, 1984;Mintzes, Trowbridge, Arnaudin, & Wandersee, 1989;Novick, 1976;Nuñez & Banet, 1997;Songer & Mintzes, 1994). As such, I, Bio should be a good test of the effectiveness of the identified design approaches in building students' meaningful understanding.…”
Section: The Performance Pbs Curriculum I Biomentioning
confidence: 99%
“…Students redesign their school lunch and activity choices to balance the calories consumed in their school lunch choices with the calories used up doing their activities. The literature shows that the seven science concepts addressed in this pPBSc are challenging to teach (Arnaudin & Mintzes, 1985;Barak, Gorodetsky, Chipman, & Gurion, 1997;Dreyfus & Jungwirth, 1989;Driver et al, 1997;Gayford, 1986;Lijnse, 1990;Mintzes, 1984;Mintzes, Trowbridge, Arnaudin, & Wandersee, 1989;Novick, 1976;Nuñez & Banet, 1997;Songer & Mintzes, 1994). As such, I, Bio should be a good test of the effectiveness of the identified design approaches in building students' meaningful understanding.…”
Section: The Performance Pbs Curriculum I Biomentioning
confidence: 99%
“…Indeed, numerous students' difficulties in connecting macro-and micro-levels in various biological topics have been previously reported (i.e. Knippels 2002; Nunez and Banet 1997;Songer and Mintzes 1994;Verhoeff 2003). Those studies indicated that students have difficulty relating biological phenomena at the macro-level with their cellular explanations (vertical coherence).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, students' difficulties in relating biological phenomena at the macro-level with their cellular and molecular explanations were also reported (i.e. Knippels 2002;Marbach-Ad and Stavy 2000;Nunez and Banet 1997;Songer and Mintzes 1994;Verhoeff 2003). Those students' difficulties were termed vertical coherence difficulties, namely, specific difficulties in understanding the functional relationships between cellular processes and the functioning of multicellular organisms (Verhoeff 2003).…”
Section: The Theoretical Basis Underlying the Studymentioning
confidence: 93%
See 1 more Smart Citation
“…En este sentido, los mapas conceptuales son una buena herramienta, y su utilización en la formación universitaria está ampliamente extendida. Su capacidad para ordenar, estructurar y jerarquizar las ideas y conceptos (Caballero y Escobar, 2006;Nousiainen, 2012) que pretendemos que nuestros alumnos trabajen, dominen y reelaboren, y su capacidad para planificar y seleccionar contenidos de enseñanza (Núñez y Banet, 1997), hacen de ella una técnica poderosa, que dota al alumnado de una herramienta multifuncional al servicio de su aprendizaje (Ibáñez y Arribas, 2012). Tales características permiten considerar a los mapas conceptuales como una actividad educativa de gran importancia para la formación docente ya que su utilización en el aula supone poner en práctica un método de trabajo activo y colaborativo (González García, 2008), comparar y debatir las concepciones de distintos maestros en formación y, además, favorecen la reflexión y la metacognición (Mellado, 2008).…”
Section: Revista Complutense De Educaciónunclassified